2017
DOI: 10.1590/s1808-185120171603173661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed Electromagnetic Field on the Consolidation of Posterolateral Arthrodeses in the Lumbosacral Spine: A Prospective, Double-Blind, Randomized Study

Abstract: Objective: To assess the effect of pulsed electromagnetic field (PEMF) on the consolidation of instrumented lumbar posterolateral arthrodeses in patients who have been surgically treated for degenerative spine disease. Methods: Forty cases were recruited from 163 consecutive patients undergoing lumbar arthrodesis at the same center. The patients were randomized into two groups of 20 patients: Active Group, who were exposed to PEMF for 4 hours a day for 90 days after surgery, and Inactive Group, who received an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…A randomized double-blind prospective study demonstrated that 92.2% of patients in PEMF treatment group had a successful fusion as determined by blinded radiographic evaluation, while the control group had a success rate of 67.9% [ 190 ]. Other clinical trials also advocated the application of PEMF for spinal fusion [ 191 , 192 ]. Conclusively, PEMF proves its benefits in clinically treating bone defects.…”
Section: Clinical Applications Of Emfs In Bone Defect Treatmentmentioning
confidence: 99%
“…A randomized double-blind prospective study demonstrated that 92.2% of patients in PEMF treatment group had a successful fusion as determined by blinded radiographic evaluation, while the control group had a success rate of 67.9% [ 190 ]. Other clinical trials also advocated the application of PEMF for spinal fusion [ 191 , 192 ]. Conclusively, PEMF proves its benefits in clinically treating bone defects.…”
Section: Clinical Applications Of Emfs In Bone Defect Treatmentmentioning
confidence: 99%